Is population's cardiorespiratory fitness really declining? - Sovová, Markéta; Sovová, Eliška; Asswad, Amjad Ghazal; Sova, Milan (Central European Journal of Public Health, 2020)
OBJECTIVE: Cardiorespiratory fitness (CRF) is defined as the capacity of the cardiovascular and pulmonary systems to meet the oxygen demands of the body during physical work. Poor CRF is connected with a higher risk for the development of various noninfectious diseases such as cardiovascular disease or malignancies. The standard test for the assessment of CRF is exercise testing with the measurement of maximal oxygen consumption (VO2 max). Standard VO2 max values for adult men and women in the Czech Republic have been available since the 1970s without being updated. According to experts, these standard values are now unusable for contemporary CRF measurements of the population in the Czech Republic. The Fitness Registry and the Importance of Exercise: a National Database (FRIEND) - 4,494 patients (1,717 men) defined new standard values for bicycle ergometry CRF for the population in the United States of America. The aim of the study was the statistical comparison of VO2 max values (reference standards) in the 1970s population in the Czech Republic with the new reference standards of the FRIEND registry. METHODS: All analyses were performed using IBM SPSS statistics and all tests with a p-value of less than 0.05 were considered statistically significant. RESULTS: VO2 max norms for women in the Czech population were higher in all age categories with statistically significant differences in the categories 30-39, 40-49 and 50-59 (p < 0.001). In the male population aged 20-29 years, VO2 max was significantly higher in the FRIEND registry (p < 0.001) in contrast to the other age categories, 30-39, 40-49 and 50-59, which were significantly higher in the Czech population (p < 0.001). CONCLUSIONS: Czech VO2 max population norms from the 1970s are (with the exception of age category 20-29 years) higher than values from the recent FRIEND registry.
Keywords: Adult; Male; lidé; lidé středního věku; Humans; Middle Aged; Exercise Test; spotřeba kyslíku; Young Adult; Czech Republic; kardiorespirační zdatnost; referenční standardy; Reference Standards; cvičení; mužské pohlaví; Oxygen Consumption; Physical Fitness; Spojené státy americké; tělesná výkonnost; dospělí; mladý dospělý; Česká republika; ženské pohlaví; Exercise; Female; United States; Cardiorespiratory Fitness; zátěžový test